Ancient Tethyan Vicariance and Long-Distance Dispersal Drive Global Diversification and Cryptic Speciation in the Red Seaweed Pterocladiella - Boo, Ga Hun; Leliaert, Frederik; Le Gall, Line; Coppejans, Eric; De Clerck, Olivier; Van Nguyen, Tu; Payri, Claude E.; Miller, Kathy Ann; Yoon, Hwan Su (Frontiers in Plant Science, 2022)
We investigated the globally distributed red algal genus Pterocladiella, comprising 24 described species, many of which are economically important sources of agar and agarose. We used DNA-based species delimitation approaches, phylogenetic and historical biogeographical analyses to uncover cryptic diversity and infer the drivers of biogeographic patterns. We delimited 43 species in Pterocladiella, of which 19 are undescribed. Our multigene time-calibrated phylogeny and ancestral area reconstruction indicated that Pterocladiella most likely originated during the Early Cretaceous in the Tethys Sea. Ancient Tethyan vicariance and long-distance dispersal have shaped current distribution patterns. The ancestor of Eastern Pacific species likely arose before the formation of the formidable Eastern Pacific Barrier – a first confirmation using molecular data in red algae. Divergences of Northeast and Southeast Pacific species have been driven by the Central American Seaway barrier, which, paradoxically, served as a dispersal pathway for Atlantic species. Both long- and short-distance dispersal scenarios are supported by genetic relationships within cosmopolitan species based on haplotype analysis. Asymmetrical distributions and the predominance of peripatry and sympatry between sister species suggest the importance of budding speciation in Pterocladiella. Our study highlights the underestimation of global diversity in these crucial components of coastal ecosystems and provides evidence for the complex evolution of current species distributions.